The Error Control Methods of Information System in Sensor Networks - Liu Wei; Lu Xing Hua (Institute of Advanced Engineering and Science, 2015)
Information System Error Discovery took a lot of interests of information system experts. Indeed, this concept has been interpreted in more than one way. This paper describes the connections between 1) the Field-to-Scope Proportion and the Identifying and Managing way of Error Discovery and 2) the (Transmission, Influence and Implementing) TII model and Error Scope. The main goal of the work described here, is to seek deeper understanding of Error Discovery in general and, at last, to find easier ways of confirming it. Second, in this paper we try to model the TII evaluating using Work Expressing System which is Relational Graph. We also use this process model to present the relationship between Error Discovery, TII, (Field-To-Scope Proportion) FSP and Error Scope. After explaining the relationship between Semantic Error and Error Discovery, we improve the Relational Graph model by adding standard. We then offer instructions of the Relational Graph.